PENGELOLAAN MEDIA INTERNAL “NEWSLETTERLEGAL & CORSEC” PT SALIM IVOMAS PRATAMA TBK JAKARTA - Haililah Tri Gandhi; Suci Destania (Universitas Mercu Buana, 2015)
The role of internal media becomes very important because through this media between employees and between employees and management can interact equate the views and objectives. Information has become the main needs of employees as the audience to meet the need for information and knowledge. The purpose of taking the object of study of the Internal Media Management